Adalimumab in severe plaque psoriasis of childhood: A multi‐center, retrospective real‐life study up to 52 weeks observation. Issue 6 (28th October 2019) - Di Lernia, Vito; Bianchi, Luca; Guerriero, Cristina; Stingeni, Luca; Gisondi, Paolo; Filoni, Angela; Guarneri, Claudio; Belloni Fortina, Anna; Lasagni, Claudia; Simonetti, Oriana; Neri, Iria; Zangrilli, Arianna; et al.
Abstract: The objective of this study is to determine drug effectiveness and safety of the tumor necrosis factor‐alpha blocker monoclonal antibody adalimumab in a real‐life cohort of 54 children and/or adolescents with severe plaque psoriasis. Retrospective, multicenter analysis over a 52‐week period is discussed in this study. Efficacy was determined by the percentage of patients achieving Psoriasis Area Severity Index (PASI 75) and PASI 90 at weeks 16, 24, and 52 and the response in biologic‐naïve versus non‐naïve patients. Safety was assessed by the number of patients experiencing at least one adverse event. At week 16, 29.6% of patients achieved a 90% PASI score reduction (PASI 90), while 55.5% of patients achieved a 75% PASI score reduction (PASI 75). Effectiveness was sustained through week 24, since PASI 90 response increased to 55.5% and PASI 75 response increased to 74.0% of patients. The PASI response rates did not differ between biologic‐naïve and non‐naïve patients. The drug was well tolerated and no serious infections were observed. Adalimumab was effective and safe in this cohort of children with severe plaque psoriasis in a 52‐week observation. Effectiveness did not differ between biologic‐naïve and non‐naïve patients.